Metabolomic and biochemical insights into bioactive compounds and antioxidant properties of black oilseed testa and peeled seeds - Habtamu Kefale; Rong Zhou; Zishu Luo; Senouwa Segla Koffi Dossou; Muez Berhe; Lei Wang; Ahmed A. Abbas; Yanxin Zhang; Ting Zhou; Jun You; Linhai Wang (Current Research in Food Science)
Black oilseed crops are rich in diverse phenolic compounds and have excellent antioxidant activities, as reported in traditional Chinese medicine. Testa (seed coat) and peeled seeds (cotyledon, embryo, and other structures) are the seed's crucial components, contributing to the variation in phytonutrient, phenol content, bioactive component, and protective and pharmacological effects. However, comprehensive and comparative information on total phenol, flavonoid, antioxidant, and metabolic profiles in black seed testa and peeled sesame, soybean, peanut, and rapeseed seeds is rare. Here, we investigated the metabolic profiles, phenolic contents, and antioxidant activities of four black oilseed crop testas and peeled seeds. This study revealed that testa has higher total phenol, flavonoid, and antioxidant activities than peeled seeds. A total of 1847 metabolites were identified across all samples and categorized into 17 major classes: flavonoids (20.02%), phenolic acids (15.15%), lipids (11.47%), amino acids and derivatives (9.36%), alkaloids (7.47%), organic acids (5.79%), terpenoids (5.68%), lignans (5.57%), saccharides (4.27%), and nucleotides and derivatives (4.17%) among the top ten. Primary class metabolites such as amino acids, saccharides, and vitamins were higher in the peeled seeds than in the testa, signifying the role of energy reservoirs and nutritive potential. However, flavonoids, phenolic acids, coumarins, chromones, lignans, terpenoids, tannins, organic acids, and lipids were abundant in the testa. Interestingly, the diversity and content of secondary metabolites were more abundant in the testa than in the peeled seeds of each crop, explaining their potential for phenol content, bioactivity, antioxidant activity, and pharmacological potential. The bioactivity of peeled seeds and testas may be associated with the phytochemical composition and content of flavonoids, phenolic acids, terpenoids, alkaloids, lipids, terpenoids, lignans, amino acids, and saccharides. Therefore, according to our results, peeled seeds offer higher nutritional value, and the testa has medicinal and protective properties. This study provides insights into the variations in phytochemical composition, phenolic content, and antioxidant activity of testa and peeled black sesame, soybean, peanut, and rapeseed seeds for further application of oilseeds in food products and to maximize nutritional benefits.